A Lateral Flow Immunochromato-graphic Strip Test for Rapid Detection of Oseltamivir Phosphate in Egg and Chicken Meat. Issue 1 (December 2018) - Yang, Xingdong; Yang, Jifei; Wang, Yinbiao; Li, Lili; Sun, Zhongke; Yue, Zonghao; Tian, Fengshou; He, Le; Hu, Xiaofei
Abstract A lateral flow immunochromatographic strip test (LFIST) based on a competitive format was developed for rapid and sensitive on-site detection of oseltamivir phosphate (OP) residues in poultry product. The sensitivity (half inhibitory concentration, IC50 ) of the LFIST in the detection of egg and chicken meat samples was confirmed to be 2.56 and 2.63 µ g/kg, and the limit detection (LOD) value were 0.43 and 0.42 µ g/kg, respectively. For intra-assay and inter-assay reproducibility, recoveries of OP spiked samples ranged between 82.8% and 91.2% with coefficients of variations (CV) less than 5.67% (intra-assay) and 6.52% (inter-assay). The performance of LFIST was comparable to high-performance liquid chromatography (HPLC) in a parallel testing of egg samples and chicken samples. LFIST takes less than 5 minutes, eliminates the dependency on professional personnel, and thus can be used as a surveillance tool for on-site detection of OP residues.